Role of the transcription factor Fli-1 on the CXCL10/CXCR3 Axis* - Wang, Xuan; Richard, Mara Lennard; Caldwell, Tomika S.; Sundararaj, Kamala; Sato, Shuzo; Nowling, Tamara K.; Zhang, Xian K. (Frontiers in Immunology, 2023)
The transcription factor Fli-1, a member of the ETS family of transcription factors, is implicated in the pathogenesis of lupus disease. Reduced Fli-1 expression in lupus mice leads to decreased renal Cxcl10 mRNA levels and renal infiltrating CXCR3+ T cells that parallels reduced renal inflammatory cell infiltration and renal damage. Inflammatory chemokine CXCL10 is critical for attracting inflammatory cells expressing the chemokine receptor CXCR3. The CXCL10/CXCR3 axis plays a role in the pathogenesis of various inflammatory diseases including lupus. Our data here demonstrate that renal CXCL10 protein levels are significantly lower in Fli-1 heterozygous MRL/lpr mice compared to wild-type MRL/lpr mice.Knockdown of Fli-1 significantly reduced CXCL10 secretion in mouse and human endothelial cells, and human mesangial cells, upon LPS or TNFα stimulation. The Fli-1 inhibitor, Camptothecin, significantly reduced CXCL10 production in human monocyte cells upon interferon stimulation. Four putative Ets binding sites in the Cxcl10 promoter showed significant enrichment for FLI-1; however, FLI-1 did not directly drive transcription from the human or mouse promoters, suggesting FLI-1 may regulate CXCL10 expression indirectly.Our results also suggest that the DNA binding domain of FLI-1 is necessary for regulation of human hCXCR3 promotor activity in human T cells and interactions with co-activators.Together, these results support a role for FLI-1 in modulating the CXCL10-CXCR3 axis by directly or indirectly regulating the expression of both genes to impact lupus disease development. Signaling pathways or drugs that reduce FLI-1 expression may offer novel approaches to lupus treatment.